Nitrogen dynamics in runoff from two small heathland catchments representing opposite extremes with respect to climate and N deposition in Norway - Kaste, Ø.; Skjelkvåle, B. L. (HAL CCSD, 2002)
International audience Effects of contrasting climatic conditions and nitrogen (N) deposition levels on streamwater N dynamics are assessed at two small heathland catchments; Dalelva in northern Norway (69°N) and Øygard in southwestern Norway (58°N). The study comprises 11 years of data on climate, hydrology and N inputs/outputs from Dalelva and 8 years of corresponding data from Øygard. Both sites are comparable in catchment size, geology and land cover characteristics, but have large differences in climate and N deposition. Dalelva is characterised by a cold, arctic climate and low N deposition (2-3 kg N ha ?1 y ?1 ), whereas the Øygard site has a more mild, humid climate with much larger N deposition (13?19 kg N ha ?1 yr ?1 ). Streamwater nitrate (NO 3 ? ) concentrations at Dalelva generally were negligible during the growing season, but showed a steady increase during the dormant season until a maximum of 40-100 ?g N L ?1 was reached just before snowmelt. At onset of the snowmelt flood, NO 3 ? concentrations decreased momentarily to very low levels, suggesting that N eluted from the seasonal snowpack to a great extent was infiltrated and immobilised in the soils. At Øygard, flood peaks occurred frequently during all seasons, and usually there was no distinct spring flood. A lack of clear dilution effects from floods on streamwater N 3 ? concentrations may indicate a relatively high NO 3 ? leaching potential in this catchment. On average, the annual NO 3 ? export was negligible at Dalelva (<0.1 kg N ha ?1 yr ?1 ), while at Øygard it amounted to 3.0±0.3 (±1 s.d.) kg ha ?1 yr ?1 , or nearly 20% of the annual N deposition. In addition to this relatively high annual N loss, elevated NO 3 ? concentrations during the growing season further indicate that the N supply at Øygard is in excess of the combined plant and microbial demand. Keywords: catchments, surface water, nitrogen deposition, nitrate leaching, climate, hydrology, snowmelt, Dalelva brook, Øygard brook